Different Proteins Mediate Step-Wise Chromosome Architectures in Thermoplasma acidophilum and Pyrobaculum calidifontis - Maruyama, Hugo; Prieto, Eloise I.; Nambu, Takayuki; Mashimo, Chiho; Kashiwagi, Kosuke; Okinaga, Toshinori; Atomi, Haruyuki; Takeyasu, Kunio (Frontiers in Microbiology, 2020)
Archaeal species encode a variety of distinct lineage-specific chromosomal proteins. We have previously shown that in Thermococcus kodakarensis, histone, Alba, and TrmBL2 play distinct roles in chromosome organization. Although our understanding of individual archaeal chromosomal proteins has been advancing, how archaeal chromosomes are folded into higher-order structures and how they are regulated are largely unknown. Here, we investigated the primary and higher-order structures of archaeal chromosomes from different archaeal lineages. Atomic force microscopy of chromosome spreads out of Thermoplasma acidophilum and Pyrobaculum calidifontis cells revealed 10-nm fibers and 30–40-nm globular structures, suggesting the occurrence of higher-order chromosomal folding. Our results also indicated that chromosome compaction occurs toward the stationary phase. Micrococcal nuclease digestion indicated that fundamental structural units of the chromosome exist in T. acidophilum and T. kodakarensis but not in P. calidifontis or Sulfolobus solfataricus. In vitro reconstitution showed that, in T. acidophilum, the bacterial HU protein homolog HTa formed a 6-nm fiber by wrapping DNA, and that Alba was responsible for the formation of the 10-nm fiber by binding along the DNA without wrapping. Remarkably, Alba could form different higher-order complexes with histone or HTa on DNA in vitro. Mass spectrometry detected HTa and Rad50 in the T. acidophilum chromosome but not in other species. A putative transcriptional regulator of the AsnC/Lrp family (Pcal_1183) was detected on the P. calidifontis chromosome, but not on that of other species studied. Putative membrane-associated proteins were detected in the chromosomes of the three archaeal species studied, including T. acidophilum, P. calidifontis, and T. kodakarensis. Collectively, our data show that Archaea use different combinations of proteins to achieve chromosomal architecture and functional regulation.